The Effect of Physical Fitness Learning Motivation and Learning Style on Physical Education Sports and Health Learning Outcomes - Mualif, Alhadj; Gusril, Gusril; Syahrastani, Syahrastani; Bahtra, Ridho (Journal of Physical Education Health and Sport, 2023)
This study aims to determine the direct and indirect effects of Learning Motivation (X1), physical fitness (X2), learning style (X3) on PJOK learning outcomes (Y). This type of research is quantitative with path analysis techniques. The population in this study were 101 students of State Senior High School 13 Kerinci. The sampling technique uses stratified random sampling, where the sample is 50 people. Data was collected by using a questionnaire to measure learning motivation (X1), the TKSI test to measure physical fitness (X2), a questionnaire to measure learning styles (X3) and student scores as PJOK learning outcomes (Y). The results of the data analysis show that the path coefficient values are normal, significant and linear, where the magnitude of the influence, both directly and indirectly, is as follows: (1) There is a direct effect of learning motivation on PJOK Learning Outcomes of students at State High School 13 Kerinci is equal to 9.12%. (2) There is a direct effect of physical fitness on PJOK Learning Outcomes in Kerinci 13 State Senior High School students of 6.50%. (3) There is a direct effect of learning style variables on PJOK Learning Outcomes of Kerinci 13 State Senior High School students of 9.24%. (4) There is an indirect effect of learning motivation on PJOK Learning Outcomes through learning styles of 16.81%. (5) There is an indirect effect of physical fitness on PJOK Learning Outcomes through style of 8.35%. (6) There is an indirect effect of learning motivation on PJOK Learning Outcomes through physical fitness of 15.1%.